Landform effect on rockfall and hazard mapping in Cappadocia (Turkey) - Zorlu, Kivanc; Tunusluoglu, M. Celal; Gorum, Tolga; Nefeslioglu, Hakan A.; Yalcin, Ali; Turer, Dilek; Gokceoglu, Candan (SPRINGER, 2011)
The Cappadocia region has unique geomorphological features resulting from differential erosional processes which make it very attractive to tourists. Besides the fairy chimneys for which the area is best known, there are also impressive buttes and mesas. Buttes and mesas are formed in regions having flat-lying strata in which the uppermost levels are composed of well-cemented limestones and granular ignimbrites, whereas the lower parts and slopes consist of low-durability tuff and ignimbrites. This durability difference results in serious rockfall events. This study involves two-dimensional rockfall analyses in and near the Avanos, Zelve, and Cavusini areas, where volcano-sedimentary units of Neogene age outcrop, to provide a rockfall hazard map in which areas of tourism activity are also considered.
Keywords: Cappadocia; Butte; Ignimbrite; Mesa; Rockfall; CENTRAL ANATOLIA; SIMULATION; Environmental Sciences & Ecology; Geology; Water Resources